Leadless pacemaker implant with concomitant atrioventricular node ablation: experience in a single center study with longterm followup. (14th October 2021) - Martinez-Sande, J.L; Garcia-Seara, J; Gonzalez-Melchor, L; Rodriguez-Manero, M; Perez-Poza, M; Fernandez-Lopez, X.A; Garcia-Vega, D; Torrelles-Fortuny, A; Gonzalez-Juanatey, J.R
Abstract: Introduction: Feasibility of concomitant leadless-pacemaker (LP) implantation plus atrioventricular node ablation (AVNA) is unknown. Moreover, safety issues in the long run are also undetermined. It seems theoretically attractive since it could avoid one additional procedure and catheter could be introduced through the same sheath employed for the LP. On the contrary, risk of dislocation/electrical variations could represent a shortcoming. Objective: We aim to report 1) feasibility of concomitant AVNA after a LP implantation and 2) long-term outcomes. Methods: Single center, prospective and observational study of 256 consecutive patients with an indication for single-chamber pacemaker placement. The implantation procedure was carried out using a femoral approach and conventional technique. Successful implantation was accomplished in 255/256 patients referred for leadless implantation. In one patient, a complete obstruction of the inferior vena cava was documented, and a conventional unicameral pacemaker was implanted. Results: 33 out of 255 patients underwent immediate AV ablation. Mean age was 75.2±8.3 years. Were predominantly females: 25 (75.7%) and indication was fast conduction atrial fibrillation (n=25), atypical flutter or atrial tachycardia (n=8). Mean acute "R wave" was 11.3mV, threshold of 0.55Vx0.24ms and impedance of 833Ω. Uneventful AV node ablation was performed in all of them immediately after LP implantation. Additional mean fluoroscopic time was 3.0 minutes. There were no vascular or arrhythmic complications after the implantation. After a mean follow-up of 27.9±12 months, all patients remained alive without notable event, and electrical parameters remained unchanged (Figure 1). Actuarial survival was shown in Figure 2. Conclusions: Conconmitant AVN ablation after LP implantation seems feasible without remarkable complications in the long run. In our experience, this approach appears more comfortable for the patients and less time-consuming than conventional pacemaker implantation with sequential AV node ablation. There were no device macrodislodgements or unexpected device malfunctions in the follow-up period. Funding Acknowledgement: Type of funding sources: None.